2006
DOI: 10.1677/jme.1.01900
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of the steroid hormone 1,25-dihydroxyvitamin D3 on the recruitment of mesenchymal lineage progenitors in fetal rat calvaria cell populations

Abstract: The steroid hormone 1,25-dihydroxyvitamin D3 (1,25(OH) 2 D 3 ) inhibits osteogenesis while stimulating adipogenesis in vitro. We hypothesized that 1,25(OH) 2 D 3 redirects the fate of osteoblast/adipocyte bipotential progenitors and other potential progenitors towards adipogenesis, a process possibly underlying the pathogenesis of osteopenic diseases such as osteoporosis. We therefore tested the global effects of 1,25(OH) 2 D 3 on the recruitment of mesenchymal progenitors including osteogenic, chondrogenic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…For instance, in contrast to the results observed in human cells, 1,25D inhibits adipogenesis in the commonly utilized 3T3‐L1 rodent cell line (Blumberg et al, ; Kong and Li, ; Lee et al, ). In other non‐human models, both stimulation (Bellows et al, ; Zhang et al, ; Mahajan and Stahl, ) and inhibition (Cianferotti and Demay, ) of adipogenesis in response to 1,25D have been reported. These discrepancies likely reflect not only different model systems (cell type, isolation protocols, differentiation media components) but also the end points reported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, in contrast to the results observed in human cells, 1,25D inhibits adipogenesis in the commonly utilized 3T3‐L1 rodent cell line (Blumberg et al, ; Kong and Li, ; Lee et al, ). In other non‐human models, both stimulation (Bellows et al, ; Zhang et al, ; Mahajan and Stahl, ) and inhibition (Cianferotti and Demay, ) of adipogenesis in response to 1,25D have been reported. These discrepancies likely reflect not only different model systems (cell type, isolation protocols, differentiation media components) but also the end points reported.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some dose response studies demonstrated that 1,25D stimulated adipogenesis at low concentrations but inhibited differentiation and induced apoptosis at high concentrations. In ex vivo cultures of fetal calvaria‐derived mesenchymal cells, 1,25D enhanced the recruitment of bi‐potential progenitors capable of differentiation along both adipogenic and osteogenic lineages (Zhang et al, ). This finding suggests that 1,25D may coordinately enhance the early stages of differentiation towards both osteogenesis and adipogenesis, a suggestion that is supported by studies in human mesenchymal stem cells (Mostafa et al, ).…”
mentioning
confidence: 99%
“…For three donors under normoxic conditions, the intrathoracic ASCs accumulated substantial intracellular lipid under osteogenic differentiation conditions, which may be related to the dexamethasone in the osteogenic formulation, as this potent corticosteroid can have inductive effects on both osteogenic and adipogenic pathways [72, 73]. Furthermore, whereas vitamin D3 has been used to stimulate osteogenic differentiation of ASCs [74], it can have diverse effects on different cell populations and has been shown in previous studies with fetal rat calvaria cells to promote adipogenesis synergistically with dexamethasone and inhibit osteogenesis [75, 76]. This phenomenon was only observed in the intrathoracic ASCs, and the differential response may indicate that these populations are more committed toward the adipogenic lineage.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, a simpler paradigm might lead to the following question: do increased levels of vitamin D improve health related quality of life and better long term outcomes? Or expressed another way, does more means better [16-18] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%